The Implementation of Project Based Learning to Improve Students' Skills in Producing Descriptive Videos about Historical Buildings - Farisah Irwayu; M. Andriana Gaffar (STKIP Yapis Dompu, 2023)
Speaking is one of the 4 aspects of English. However, not a few students experience difficulties in speaking English because they often make mistakes in pronouncing vocabulary. And a teacher is always required to be able to develop learning methods to improve students' speaking skills at school. The purpose of this study is to find out how to implement project based learning to improve students speaking skills by making descriptive videos about historical buildings and how students respond to the use of project based learning in class. This study uses qualitative research methods with an action research approach. The instruments used by researchers are observations, field notes, and interviews. Participants in this study were 20 students of class X IPA 2 SMA PGRI 2 Bandung. Research data in cycle 1 shows that the average score of students' English speaking ability is 71.5 with a maximum score of 80, and data in cycle 2 shows that there is an increase in students' ability as evidenced by the increase in students' average score to 85 with a maximum score of 95 This data is also supported by student responses which say that students like learning activities using project based learning because students are given more opportunities to practice their speaking skills. Based on the research results, it can be concluded that the implementation of project based learning in producing descriptive videos about historical buildings can improve students' speaking skills and can be used efficiently in class.